Pfeiffer Syndrome Type 2 : Prenatal diagnosis. Case report and literature review - Huertas Tacchino, Erasmo (2019)
Pfeiffer syndrome is an autosomic dominant disorder characterized by craniosynostosis, midface hypoplasia and syndactyly of the hands and feet. Three different phenotypes have been described, where type 2 is the most severe and the one amenable of prenatal diagnosis. We present the first clinical case reported at Instituto Nacional Materno Perinatal, Lima, Peru, of a fetus with suspicious ultrasound prenatal findings of this syndrome including cloverleaf-shaped skull, severe ventriculomegaly, frontal bossing, ocular proptosis and overlapped fingers, who was born by cesarean section and died at day eight due to progressive respiratory distress.